Searching to Eliminate Personal Information Management - Cutrell, Ed; Dumais, Susan; Teevan, Jaime (Communications of the ACM (CACM), 2006)
Search systems can alleviate the need to organize personal information by helping us find it no matter where we encountered it, what we remember about it, and even if we forget it exists.